Study of Functional Outcome in Terms of Pain and Range of Movements in Degenerative Rotator Cuff Tear by Transosseous Sutures in Elderly - Taralekar, Gautam TaralekarGautam A; Shinde, Girish; Martyres, Sasha; Shetti, Sachin G; Singh, Lokesh (Archives of Clinical and Biomedical Research, 2021)
Introduction: The surgical treatment of Rotator cuff repair ranges from open to arthroscopic assisted mini open repair to full arthroscopic repair. The anterior approach or lateral deltoid approach has its advantages and disadvantages depending upon the site and the extent of the rotator cuff tear. Aim and objective: To assess the functional outcome of mini-open anterolateral approach for degenerative rotator cuff tear by trans-osseous sutures in elderly in terms of pain and range of movements. Methodology: The present study was prospective observational study conducted on Patients with degenerative rotator cuff tears presenting at Department of Orthopaedics. Patients underwent mini-open anterolateral approach for degenerative rotator cuff tear by trans-osseous sutures. Follow-up of patients was done immediate after suture removal, at six weeks, at twelve weeks, twenty-four weeks following the surgery. Pre-op and Final follow up evaluation was done for each patient using VAS scale and range of movement. Shoulder index using ASES scores were noted. Results and discussion: Majority of the patients (52%) were males and (48%) were females. 44% cases were between 61 to 70 years of age. In our study in follow up at 6,12, 24 weeks, range of motion was found to be increasing during subsequent follow ups. (p<0.001) The average ASES scores improved from 20.83 to 81.15 (Range 58-67) at final follow up (p<0.0001).